Utero cutaneous fistula after caesarean section: a case report - Kucha, Kalpesh; Vaishnav, Himanshu; Damor, Pradeep; Yagnik, Ami; Desai, Gayatri; Maitra, Nandita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Uterocutaneous fistula is a rare pathology which occurs most commonly after a caesarean section. This is the case report of a 26-year-old patient who presented soon after her second caesarean section, with an abdominal nodule and cyclical pain and discharge from it. A pelvic MRI confirmed the diagnosis. Surgical management was successful.